2020
DOI: 10.1002/hyp.13862
|View full text |Cite
|
Sign up to set email alerts
|

The variation and controls of mean transit times in Australian headwater catchments

Abstract: Determining mean transit times in headwater catchments is critical for understanding catchment functioning and understanding their responses to changes in landuse or climate. Determining whether mean transit times (MTTs) correlate with drainage density, slope angle, area, or land cover permits a better understanding of the controls on water flow through catchments and allows first‐order predictions of MTTs in other catchments to be made. This study assesses whether there are identifiable controls on MTTs deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
0
9
0
1
Order By: Relevance
“…These are compounded by logistical challenges of sampling in often large, remote catchments. Cartwright et al (2020) used tritium dating of streamflow in a number of mesoscale catchments in Victoria to ascertain Mean Transit Times of base flows and to relate these to potential climatic and landscape controls.…”
Section: Water Ages In Seasonally Wet Catchments In Australiamentioning
confidence: 99%
“…These are compounded by logistical challenges of sampling in often large, remote catchments. Cartwright et al (2020) used tritium dating of streamflow in a number of mesoscale catchments in Victoria to ascertain Mean Transit Times of base flows and to relate these to potential climatic and landscape controls.…”
Section: Water Ages In Seasonally Wet Catchments In Australiamentioning
confidence: 99%
“…Other lumped parameter models such as the gamma (GM) or dispersion (DM) models could also have been used; the GM(α = 3) and DM(D P = 0.22) models produce distributions that are closely equivalent to the EPM(f = 0.7) curve (Stewart et al, 2017). Cartwright et al (2018) also showed that numerical models that include dispersion yield similar curves; such models are independent of the lumped parameter model approach.…”
Section: The Current Situation Of Tritium In Precipitationmentioning
confidence: 99%
“…A recent summary of tritium results from Australian catchments illustrates the capacity of tritium to identify old water in SH catchments (Table 1, Cartwright et al, 2020;Duvert et al, 2016). These MTTs are much longer than could be estimated by stable isotopes, so they show that truncation is very much an issue.…”
Section: Evidence That 3 H Ttds Can Be Different From 2 H Ttdsmentioning
confidence: 99%
“…Aprimorando o trabalho descrito anteriormente, CARTWRIGHT et al (2020) expandiram para quatro o número de cabeceiras de bacias hidrográficas estudadas na região sudeste da Austrália, utilizando a mesma metodologia, resultando em 29 sub-bacias. Os autores explicitam a necessidade de incrementar os estudos relacionando o tempo médio de residência e as características das bacias, de modo a revelar as relações que controlam o sistema.…”
Section: Aplicações Do Trítio Ambiental Em Bacias Hidrográficasunclassified